Pengembangan Bahan Ajar Mata Kuliah Pembelajaran IPS SD Untuk Mahasiswa PGSD Universitas Bhinneka PGRI - Ria Fajrin Rizqy Ana (INVENTA: Jurnal Pendidikan Guru Sekolah Dasar, 2020)
The purpose of this research is to develop teaching materials for SD social studies subjects and to increase learning motivation of PGSD students at Bhinneka PGRI University. The method used is research and development (R&D) with the Four D (4D) development model. The 4D development model consists of 4 stages, namely: Define, Design, Develop and Disseminate. The instruments used were questionnaires and test questions. The results showed that from individual trials the results obtained were 87.5%, small group trials (12) of 84.17% students, field trials on 37 students obtained 90.88% results, so that the book product was suitable for use in learning activities.